Sovereign Debt Repatriation During Crises - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2022)
We use a new, comprehensive data set on the sovereign debt investor base to document three novel empirical facts: (i) sovereign debt is repatriated - that is, shifted from external private to domestic investors - prior to sovereign defaults; (ii) not all crises are equal: evidence for repatriation during banking and currency crises is more limited; and (iii) the nature of defaults matters: external investors do not leave during preemptive debt restructurings. We further show that repatriation appears to be prevalent when defaults happen in large markets with low capital controls. The data set we use is uniquely suited to analyzing investor base dynamics during rare crises due to its large cross-section and time series, covering 180 countries from 1989 to 2020.